New species and records of Algonina Schillhammer & Brunke, 2018, mainly from China - Li, Chong; Tang, Liang (Zootaxa, 2023)
Five new species of the subtribe Algonina Schillhammer & Brunke, 2018 from China are described: Algon. kuankuoshuiensis sp. n. from Guizhou, A. daweishanus sp. n. from Yunnan, A. pseudotibetanus sp. n. from Xizang, A. huadongensis sp. n. from Zhejiang and Fujian, and Barypalpus maoershanus sp. n. from Guangxi. A new species group, Algon tibetanus species group, is established. Males of Algon tibetanus Schillhammer, 2006 and A. malayanus (Cameron, 1950) are discovered for the first time. Algon bramlettorum Schillhammer, 2006 is newly recorded from China. Additional records for nine species of Algon and one species of Barypalpus are provided. Diagnostic characters for new species are described and illustrated. A key to the genera of Algonina and a key to the Chinese species of Algon are provided.